A Dinuclear Ruthenium(II) Polypyridyl Complex Containing A terpy‐like Fragment for Cu2+ Probing1. Issue 8 (4th April 2014) - Cheng, Feixiang; Tang, Ning; Miao, Kaicheng; Wang, Fan
Abstract The dinuclear RuII complex [{Ru(bpy)2}2(μ2‐H2L)]4+ (bpy = 2, 2'‐bipyridine, H2L = 2, 6‐bis{4‐(1, 10‐phenanthroline‐[5, 6‐d]imidazol‐2‐yl)}pyridine) was synthesized and characterized. The effects of the cation on the UV/Vis absorption and fluorescence spectra as well as the electrochemical properties of the complex were studied. It served as a fluorescent sensor with high selectivity and sensitivity toward Cu2+ among 17 metal ions. The complex showed 2:1 binding ratio with Cu2+ in H2O/CH3CN solution (1:1, v/v) with a high binding constant of 2.69 × 1011 M–1.